Identificando a Relação Virtual Entre Empresas Explorando Reações de Usuários no Facebook - Tsutsumi, Diego P.; Fenerich, Amanda T.; Silva, Thiago H. (Anais do Workshop de Computação Urbana (CoUrb), 2018)
We live today in a highly competitive world in many areas, including the business world. Thus, strategic business partnerships are important for a business to succeed, especially for those exposed to a dynamic and uncertain market. Therefore, this study aims to identify expressive virtual relationships between companies that are generated spontaneously by users in social media. To this end, a business similarity model based on common spontaneous reactions of users in social media, particularly Facebook, is proposed, as well as a new algorithm for detecting business communities within the proposed model. To demonstrate the proposed methodology, the study uses more than 280 million user reactions on Facebook about companies in Curitiba, Brazil. Exploring these data and the proposed methodology, this study shows the possibility to identify non-trivial relations between companies, which may enable the development of new mechanisms for recommending strategic business partnerships for entrepreneurs and business owners.